Food Choice Determinants of Island Tourists: an Implication Towards Sustainable Island Tourism - Ahmad Puad, Mat Som; Wan Hafiz, Zainal Shukri; Fathilah, Ismail; N Alia Fahada, W Ab Rahman (2018)
This study aims to investigate factors that influence food choice of international tourists at small island settings. In this study, Perhentian Island was selected as a representative of small islands as the island received the largest number of international tourists, particularly in the East Coast of Peninsular Malaysia. A close-ended questionnaire survey was conducted at various tourism spots in Perhentian Island and a total of 173 international tourists were interviewed in this study. Descriptive analysis was applied to summarize the tourists profile and travel pattern. Satisfaction gap analysis generated important factors that influence food choice among island visitors. As the majority of the international tourists to island destinations in Malaysia were on a multi-destination vacation, the results of the study could be crucial to the real needs and expectations of island tourists in Malaysia. Finally, effective development and marketing strategies could be devised to enhance the growth of food tourism, targeting remote island destinations in Malaysia.